The contemporary observations of paradiplomacy: the case of Sabah-Australia connections - Rizal Zamani Idris; Rafiq Idris; Azizan Morshidi (Human Resource Management Academic Research Society, 2021)
Diplomacy has always been seen as a state-centric matter that views state as the only actor in international relations. Nevertheless, since the end of the Cold War, this belief has been challenged with the growing role of multinational as well as sub-state entities in international political arena. Malaysia-Australia relations have been shaped with numerous issues and challenges. Despite their bumpy political ties in the past (especially during the prime ministership of dr. Mahathir Mohamad) other spheres of the relationship remained unaffected. As such, a case study is conducted by looking at Sabah-Australia relations in terms of paradiplomatic practices. This research is qualitative in nature. Initial findings indicate that historical imperatives as well as trading interactions are two forms paradiplomatic practice that has contributed to strengthening of Malaysia-Australia relations.